Efficacy of transcranial direct current stimulation on tension-type headache and migraine: A systematic review - Gupta Saloni; Goel Deepak; Mishra Preeti; Garg Shobit; Singhal Tushar (Indian Journal of Pain, 2022)
Introduction: Headache is one of the most common conditions troubling nearly 68% of the world's population. Tension-type headache (TTH) & migraine are the most common forms of classical headaches, which is nowadays mostly neglected, associated with frequent, severe pain and significant functional impairment. Transcranial direct current stimulation (tDCS), is a non-invasive, painless brain stimulation treatment that uses direct electrical currents to stimulate specific parts of the brain. Various studies demonstrated tDCS as a valued device to treat neuropsychiatric conditions such as chronic headache & associated anxiodepressive condition. Objective: The aim of this the current review was to evaluate the effectiveness of tDCS in the management of TTH and Migraine. Results generated from various studies for the effectiveness of tDCS in TTH & Migraine. Methods: We programmed our search strategy, to identify studies pertaining to use of tDCS and pain management in TTH & migraine, within the Database of the Cochrane Library of Systematic Reviews, & various author manuscripts in PMC, MEDLINE, EMBASE, NLM, PsycINFO, Other indexed citations from inception to December 2021 and potentially relevant studies. Outcomes: The outcomes of interest include: Effective pain management, in terms of headache intensity, frequency, its episodes, associated depression, anxiety, in target population prioritised by the individual reviews. The evidences were mapped and synthesised with appropriate health problem, patient subgroups, intervention type, context and outcome.Conclusions: We found a significant reduction of pain intensity in patients receiving tDCS treatment, also the pain intensity and duration were significantly improved from baseline after tDCS treatment and during a follow-up period. There was a significant reduction of pain intensity by both anodal and cathodal stimulation conditions, with noteworthy decrease in episodic headaches equally by both 1mA and 2mA current intensities. The aforementioned works support the utility of tDCS in the pain management of TTH and migraine offering a hope for patients with this debilitating disease. However, the review shows promising results in the pain management by tDCS, but the included studies must be analysed critically since most of them were pilot studies, with some having adapted an open-label design.